Researching Intercultural Learning
XVI, 287 p.
Keywords: International perspectives on intercultural learning are presented within a framework of cultures of learning related to education and language learning and use in academic contexts. Intercultural learning involves learners travelling to learn in a place where other cultures of learning are dominant and to which they are usually expected to adapt.